2003
DOI: 10.1007/s00381-002-0701-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of cine flow MRI in children with Chiari I malformation

Abstract: Introduction: Since the introduction of MRI, the incidence of Chiari I malformations (cerebellar tonsils ectopia) has increased. The clinical significance of this finding remains questionable in some instances. Recently, cine flow MRI has added to the understanding of the dynamics of cerebrospinal fluid at the craniocervical junction and to the pathophysiology of the Chiari I malformation. The present study attempts to analyze the role of cine flow MRI in Chiari I malformations. Materials and methods: Between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(52 citation statements)
references
References 25 publications
1
45
0
4
Order By: Relevance
“…In recent years, investigators have published several series examining the outcome from extradural decompression for CM1 compared to the more-invasive decompression with duraplasty [8, 13, 16, 17, 2224]. Such studies have focused primarily on operative morbidity, postoperative complications rates, and repeat surgery for persistent disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, investigators have published several series examining the outcome from extradural decompression for CM1 compared to the more-invasive decompression with duraplasty [8, 13, 16, 17, 2224]. Such studies have focused primarily on operative morbidity, postoperative complications rates, and repeat surgery for persistent disease.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies, including a meta-analysis by Durham and colleagues [6, 13, 17], have found PFDO associated with higher rates of reoperation for persistent disease, evidence suggesting a difference in symptomatic outcome is mixed [8, 13, 23, 24]. Though not statistically significant in meta-analysis, some findings also show higher rates of syrinx improvement in patients undergoing PFDD [6, 17, 22], leading many physicians to avoid extradural decompression in patients with syringomyelia [20]. However, these previous studies had important limitations: first, these studies lacked treatment groups that were balanced on demographic variables, presenting symptoms, and radiographic findings; second, the methods used to report clinical outcomes were poorly defined and not based on any validated metrics.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of Chiari type I malformation in patients with or without symptoms is established with neuroimaging techniques; the preferred technique is magnetic resonance imaging (MRI) [20]. MRI can also be used to study the volume of the posterior fossa and CSF flow dynamics.…”
Section: Diagnosismentioning
confidence: 99%
“…The role of the medical professional is to provide up-to-date information, such as details of referrals and recommendations for other professionals, investigations developed, and recommended therapies [20]. …”
Section: Psychological Issuesmentioning
confidence: 99%
“…Other groups have published case series with outcomes split into “better, unchanged, or worse” categories. 5,9,13,17,18 A similar assessment algorithm has been in use at our institution, though this classification is highly subjective and poorly suited for assessing outcomes within or between individuals. More recently, the Chicago Chiari Outcome Scale (CCOS) was developed to address outcomes with a more complete approach to the variety of symptoms patients may experience (see Table 1).…”
Section: Introductionmentioning
confidence: 99%